Syngas production from ethanol dry reforming using cu-based perovskite catalyst - Ramkiran, Attili; Labhsetwar, Nitin; Phuong, Pham T. T.; Truong, Quang Duc; Vo, Dai-Viet N.; Mohd Sabri, Mahmud (Universiti Malaysia Pahang, 2019)
This paper reports about production of syngas from dry reforming of ethanol (EDR) by using LaCuO3 and CeCuO3. The catalysts were prepared via the citrate sol-gel method and characterized by BET, TPO, H2-TPR, FTIR, HR-TEM, SEM-EDX and XPS. The EDR tests were run in a stainless-steel fixed-bed reactor under the atmospheric pressure. Gas hourly space velocity, GHSV = 42 Lgcat-1h-1 and mean particle size 100 – 140 µm were used for all runs to ensure the negligible internal and external mass transport resistance. The X-ray diffraction analysis of LaCuO3 and CeCuO3 catalysts registered the phases of CuO, La2O3, CeO2 and LaCuO3 on the surface of the catalysts after calcination. The ethanol and CO2 conversions were increased at excess CO2 feed and decreased at excess ethanol feed under the pressure varied from 20-50 kPa. The metallic states of Cu, La2O3 and CeO2 were confirmed with the XRD and XPS analysis. Two peaks of metal oxidation were recorded by H2-TPR for both catalysts where LaCuO3 showed lower reduction than CeCuO3. Result of FTIR showed C-O, C-H and hydroxyl group beside metal oxides. The catalytic activity of LaCuO3 is higher than the CeCuO3 catalyst at stoichiometric ratios (Ethanol/CO2: 1/1), 1023 K with the ethanol and CO2 conversions of 74 and 18 % respectively.